Neuroglia in cognitive reserve - Alexei Verkhratsky; Robert Zorec (2024)
Abstract The concept of cognitive reserve was born to account for the disjunction between the objective extent of brain damage in pathology and its clinical and intellectual outcome. The cognitive reserve comprises structural (brain reserve) and functional (brain maintenance, resilience, compensation) aspects of the nervous tissue reflecting exposome-driven life-long plasticity, which defines the ability of the brain to withstand aging and pathology. The mechanistic background of this concept was primarily focused on adaptive changes in neurones and neuronal networks. We present arguments favoring the more inclusive view, positing that neuroglia are fundamental for defining the cognitive reserve through homeostatic, neuroprotective, and neurodegenerative mechanisms. Neuroglia are critical for the life-long shaping of synaptically connected neuronal circuits as well as the brain connectome thus defining cognitive reserve. Neuroglial homeostatic and protective physiological responses define brain maintenance and resilience, while neuroglia regenerative capabilities are critical for brain compensation in pathology. Targeting neuroglia may represent an untrodden path for prolonging cognitive longevity.